Determinan Perilaku Penggunaan Kontrasepsi Pasca Persalinan di Wilayah Kerja Puskesmas Merdeka Kota Bogor - Agustina Agustina; Nawati Nawati (Jurnal Kesehatan, 2017)
Contraceptive use by women of reproductive age nationwide showed decreased from 61.4% (2007) to 55.86% (in 2010). In West Java amounted 59.8%. Unmet need in Indonesia is 14% and in West Java is 11.1%. Achievement of the family planning program active participant in Bogor reached 78.61% and the achievement of a new family planning program postpartum still low at 49.53% (BPMPM, Bogor 2013). The Purpose of research is to find out the determinant behavioral of contraceptive use post-natal in health center Bogor 2014.This research is quantitative with the design "Cross Sectional" study sample group of mothers aged 15-49 are married, have babies ages 6 weeks to 12 months is 111 respondents. The sampling technique is purposive sampling. The results of the bivariate analysis showed there is relation antenatal/ Ante Natal Care contraceptive use with p=0.031 and the value of OR=0.2 (95% CI=0.44 to 0.9). This means that mothers during their pregnancy ≥4 times have a great opportunity for not using contraception post partum was 0.2 times. Suggested to the health nurse at the health center in order to improve quality of care through counseling activities on family planning and counseling about contraception postpartum starting from pregnancy and continues into the postpartum period.